A Review of The Effectiveness of Independent Outpatient Registration Through The Mobile JKN at Sukosari Health Center and Manguharjo Health Center in Madiun City - Ardianingrum, Al Wafi Rahmaputri; Apriani, Dika; Apriliani, Eltigeka Devi (Procedia of Engineering and Life Science, 2024)
Law Number 40 of 2004 stipulated that the National Social Security System mandates social security for all Indonesian citizens, namely the National Health Insurance (JKN). The Mobile JKN application provides an essential service to the public online, eliminating the need for long queues at health institutions. Research conducted from July 2022 to April 2023 showed that of the 196,917 residents of Madiun City, only 46 participants used the Mobile JKN application. The low enthusiasm for registering independently for outpatient services through Mobile JKN is attributed to either the inability to use the application or the inadequate quality of the service. This study employed a descriptive quantitative design based on observations. The results showed that the application process for Mobile JKN at health centers in Madiun City aligned with technology acceptance. Overall effectiveness was deemed "successful," with a percentage score of 79.02%, attributed to the application's quick access time, reliable information, and prompt handling of consumer complaints. Madiun City health centers encourage the public to use the Mobile JKN application by promoting it through leaflets and social media.